Community Participation in The Development of Clean Water Infrastructure in Maholo Village, East Lore District Poso Regency - Gilbert Ceasar Abu; Irwan Waris; Angga Pradana (Green Publisher Indonesia, 2026)
The availability of clean water is a basic need that has a direct impact on the quality of life of rural communities. However, the development of clean water infrastructure in Maholo Village, East Lore District, Poso Regency, still faces challenges, particularly regarding suboptimal community involvement and the slow response of officers in handling field issues. This study aims to analyze community participation in the development of clean water infrastructure in Maholo Village by referring to the three stages of participation according to Cohen and Uphoff (1979): planning, implementation, and utilization of results. This research employs a qualitative method with a descriptive approach and is based on the theory of community participation by Cohen and Uphoff (1979), which includes planning, implementation, and utilization. The informants consist of five individuals: the Village Head, the Head of the Village Consultative Body (BPD), a clean water officer, a community leader, and a water user. Data were collected through interviews, observation, and documentation. The results show that community participation remains suboptimal and tends to be passive. In the planning stage, community involvement is still limited. In the implementation stage, participation remains low. Meanwhile, in the utilization stage, the community has benefited from the existing infrastructure; however, there are still complaints regarding service quality, particularly the slow response of officers in handling damages and water distribution disruptions. In conclusion, community participation needs to be improved, particularly in the planning and implementation stages, as well as through enhancing service quality. Therefore, it is necessary to strengthen communication, transparency, and responsiveness between the village government and the community to support the sustainability of clean water infrastructure management.